Return to play after hip arthroscopy among tennis players: outcomes with minimum five-year follow-up - David R. Maldonado; Mitchell J. Yelton; Philip J. Rosinsky; Jacob Shapira; Mitchell B. Meghpara; Ajay C. Lall; Benjamin G. Domb (BMC Musculoskeletal Disorders, 2020)
Abstract Background Playing tennis is associated with various movements that can lead to labral injuries and may require arthroscopic surgery. While hip arthroscopies have demonstrated good outcomes in athletes, there is limited literature reporting patient reported outcomes (PROs) and return to sport (RTS) in competitive or recreational tennis players after arthroscopic hip surgery. Therefore, the purpose of the present study was to (1) report minimum five-year PROs and RTS in tennis players who underwent arthroscopic hip surgery and (2) compare outcomes between recreational and competitive tennis players. Methods Data for patients who underwent hip arthroscopy surgery in the setting of femoroacetabular impingement and labral tears between March 2009 and January 2014 and who played tennis within one-year of surgery were retrospectively reviewed. Patients with preoperative and minimum five-year postoperative scores for the following PROs were included: modified Harris Hip Score (mHHS), Non-Arthritic Hip Score (NAHS), Hip Outcome Score-Sport Specific Subscale (HOS-SSS), and visual analog scale (VAS) for pain. Patient Acceptable Symptomatic State (PASS) and Minimal Clinically Important Difference (MCID) for mHHS and HOS-SSS were calculated. Results Of 28 patients, 31 hips met all inclusion and exclusion criteria of which 28 (90.3%) had minimum 5-year follow-up (mean: 72.8 ± 13.9 months). There were 3 professional, 3 collegiate, 2 high school, 2 organized amateur, and 18 recreational level tennis players. All PROs significantly improved at latest follow-up: mHHS from 67.0 to 86.7 (P <  0.001), NAHS from 65.9 to 87.2 (P <  0.001), HOS-SSS from 50.0 to 77.9 (P = 0.009), and VAS from 5.4 to 1.8 (P <  0.001). There was a 75.0% RTS rate. Additionally, 66.7% of patients achieved MCID and 83.3% achieved PASS for mHHS, and 63.6% achieved MCID and 58.3% achieved PASS for HOS-SSS. Conclusion Regardless of the level of participation, tennis players who underwent arthroscopic hip surgery reported statistically significant PRO improvements. A favorable rate of RTS was also achieved by players with a continued interest in playing. The data here may be useful in counseling tennis players of various levels who are considering arthroscopic treatment of a hip injury. Level of evidence IV